Attapulgite-based hierarchical pore HZSM-5 molecular sieve supported iron-based catalyst and its application in the preparation of aromatics from syngas

By using concave and concave rock stone modification to prepare multi-stage pore HZSM-5 molecular sieve and loading iron-based catalysts, the complex and cost-effective catalyst preparation in the prior art is solved, efficient CO conversion and aromatic selectivity are achieved, and good industrial application prospects are provided.

CN116943713BActive Publication Date: 2025-03-28GUANGZHOU INST OF ENERGY CONVERSION CHINESE ACAD OF SCI
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202310767411.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-27
Publication Date
2025-03-28
Estimated Expiration
2043-06-27

AI Technical Summary

Technical Problem

The existing high-performance HZSM-5 molecular sieve catalyst preparation requires complex post-treatment processes and high-cost silicon and aluminum sources, and their activity is low and the CO2 by-product selectivity is high, making it difficult to achieve industrial application.

Method used

The in situ formation of multi-stage pore HZSM-5 molecular sieve is used as raw material, and the in-situ formation of a multi-stage pore HZSM-5 molecular sieve is achieved by acid modification, and an iron-based catalyst is supported by an equal volume impregnation method to prepare a catalyst with a microporous-mesoporous multi-stage pore structure.

Benefits of technology

It reduces the cost and energy consumption of catalyst preparation, improves CO conversion and aromatic selectivity, reduces the carbon deposit of catalysts, extends service life, and has good industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116943713B_ABST
    Figure CN116943713B_ABST
Patent Text Reader

Abstract

The present invention discloses an attapulgite-based multi-level hole HZSM-5 molecular sieve loaded iron-based catalyst and its application in the preparation of aromatics from synthesis gas. The attapulgite-based multi-level hole HZSM-5 molecular sieve loaded iron-based catalyst is an acid-modified attapulgite as a silicon source and an aluminum source, tetrapropylammonium bromide or tetrapropylammonium hydroxide as a main template, three-dimensional ordered macroporous polymethyl methacrylate as an auxiliary template, hexadecyltrimethylammonium bromide as a structure directing agent, and deionized water as a solvent, and a hydrothermal method is used to synthesize the attapulgite-based multi-level hole HZSM-5 molecular sieve; iron is then used as a single active component, and it is loaded on the attapulgite-based multi-level hole HZSM-5 molecular sieve by an isovolumetric impregnation method to obtain a target catalyst. Using the catalyst proposed by the present invention, under preferred conditions, it can be achieved that the CO single-pass conversion rate reaches more than 90%, the aromatics selectivity reaches 60%, and the molecular sieve does not need a post-processing process, the catalyst preparation process is simple, the cost is low, and there is a good prospect for industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of energy chemical industry, and in particular to an attapulgite-based multi-level-pore HZSM-5 molecular sieve-supported iron-based catalyst and application thereof in preparing aromatics from synthesis gas. Background Art

[0002] Aromatic hydrocarbons are important bulk organic chemical raw materials. According to the number of benzene ring structures, they are mainly divided into monocyclic aromatic hydrocarbons, polycyclic aromatic hydrocarbons and condensed aromatic hydrocarbons, etc. They are widely used in the production of various polymers such as nylon, polyester, resin, polyurethane, film, etc. According to statistics, my country's demand for benzene, toluene and xylene in 2021 will reach 63.09 million tons, while the output will be only 46.38 million tons. There is still a large gap that needs to be imported from abroad. It can be seen that the contradiction between the growing demand for aromatic hydrocarbons in my country and the insufficient domestic production capacity has become the key to restricting the development of the manufacturing industry. In view of the characteristics of my country's energy structure of "rich in coal, less gas, and poor in oil", it is urgent to develop new non-petroleum-based aromatic hydrocarbon production technologies.

[0003] In recent years, the production of aromatics from coal, biomass, natural gas or CO2 via synthesis gas (H2 / CO) intermediates has received widespread attention. At present, the preparation of aromatics from syngas mainly includes two routes: the indirect method and the direct method. The indirect method is to convert the syngas into a methanol intermediate first, and then the methanol undergoes an aromatization reaction on a molecular sieve to produce aromatics. This process has not yet been industrialized; the direct method includes two categories. One is that the syngas is first converted into an intermediate product olefin, methanol, ethylene ketone or dimethyl ether in a first reactor over a metal oxide catalyst, and then an aromatization reaction is carried out over a molecular sieve catalyst in a second reactor to produce aromatics. For example, Chinese patents CN106215972A and CN106540740A disclose a catalyst containing a Zr-based oxide and a zeolite molecular sieve for preparing aromatics from syngas via a methanol / dimethyl ether intermediate, and Chinese patents CN 106607083A, CN 110385141A and CN105944751A disclose a composite molecular sieve containing an Fe-based composite oxide and a zeolite molecular sieve for preparing aromatics from syngas via an olefin intermediate. However, this type of catalyst is limited by thermodynamics, and its activity is usually less than 50%, and the selectivity of CO2 byproduct is high. Another type is a one-step method, in which synthesis gas is directly used to produce aromatics in a single reactor under the action of Fe-based or Co-based bifunctional composite catalysts. For example, Chinese patents CN 106268924B and CN 111375444B disclose a method of using a modified HZSM-5 molecular sieve or a nano-multi-level pore ZSM-5 molecular sieve to load an Fe-based catalyst for direct production of aromatics from synthesis gas in a one-step method. This type of catalyst has high CO conversion rate and aromatics selectivity, and mild reaction conditions, and has good prospects for industrial application.

[0004] At present, the acidic molecular sieve used in the catalyst for the conversion of syngas to aromatics is mainly HZSM-5 molecular sieve. HZSM-5 has a certain number of strong / weak acid centers, which helps olefins to cyclize at the acid site to generate aromatic products; there are two types of pores, zigzag and straight, and its pore structure is close to the kinematic size of aromatics, which helps the aromatic products to diffuse in the pores. The use of different metals to modify HZSM-5 can adjust the acid strength and density. Through desiliconization or dealuminization, the number of mesopores of the molecular sieve can be increased or a hollow structure can be formed, thereby improving aromatic selectivity, reducing carbon deposition, and extending the service life of the catalyst (Journal of Fuel Chemistry, 2023, 51(1): 52-66). It can be seen that the existing high-performance HZSM-5 molecular sieves require relatively complex post-processing procedures. The silicon source and aluminum source used in the synthesis process are generally ethyl orthosilicate and aluminum isopropoxide. If a new low-cost raw material can be developed and a multi-level pore structure can be formed in situ during the synthesis process, it will inevitably significantly reduce the cost and energy consumption of molecular sieve synthesis.

[0005] Attapulgite is a natural clay mineral with a special layered chain structure and rich in magnesium aluminum silicate. It has a large specific surface area, stable electrochemical properties, a nanofibrous morphology, high dispersibility, good thermal insulation, high adsorption capacity and strong bonding force. It has been widely used in various industries. Attapulgite is rich in SiO2, CaO, MgO and Al2O3, and is a natural multiphase catalyst carrier material. The specific surface area and pore structure, surface groups and acidity and alkalinity, surface hydrophilicity / hydrophobicity and adsorption sites of attapulgite can be effectively adjusted by acid and alkali activation or inorganic oxide pillaring. In addition, attapulgite contains a small amount of Fe, K, Na and other active or auxiliary metals that can be used as catalysts for the one-step synthesis of aromatics. It is an excellent carrier for the synthesis of Fe-based or Co-based bifunctional composite catalysts. However, there is no report on the use of attapulgite in the preparation of multi-level pore HZSM-5 molecular sieves and its application in the one-step synthesis of aromatics from syngas. Summary of the invention

[0006] The present invention provides an attapulgite-based multi-level pore HZSM-5 molecular sieve supported iron-based catalyst and application thereof in preparing aromatic hydrocarbons from synthesis gas. The attapulgite is used as a raw material and is used for synthesizing the multi-level pore HZSM-5 molecular sieve and the supported nano-iron-based catalyst after acid modification. The prepared catalyst has a microporous-mesoporous multi-level pore structure, can promote the diffusion and escape of aromatic hydrocarbon molecules, improve the CO conversion rate and aromatic hydrocarbon selectivity, and reduce the catalyst preparation cost.

[0007] The present invention is achieved through the following technical solutions:

[0008] A attapulgite-based multi-level pore HZSM-5 molecular sieve supported iron-based catalyst is prepared by the following steps: using acid-modified attapulgite as a silicon source and an aluminum source, tetrapropylammonium bromide or tetrapropylammonium hydroxide as a main template, three-dimensional ordered macroporous polymethyl methacrylate (PMMA) as an auxiliary template, hexadecyltrimethylammonium bromide (CTAB) as a structure directing agent, and deionized water as a solvent, and synthesizing the attapulgite-based multi-level pore HZSM-5 molecular sieve by a hydrothermal method; and then using iron as a single active component, and supporting it on the attapulgite-based multi-level pore HZSM-5 molecular sieve by an equal volume impregnation method, so as to obtain the attapulgite-based multi-level pore HZSM-5 molecular sieve supported iron-based catalyst.

[0009] The invention adopts natural attapulgite as a raw material to prepare a nano multi-level pore HZSM-5 molecular sieve loaded with an iron-based catalyst, avoids the use of chemical reagents such as tetraethyl orthosilicate and aluminum isopropoxide, and simultaneously utilizes the synergistic effect of a template agent and a structure directing agent to realize the in-situ formation of a microporous-mesoporous multi-level pore structure molecular sieve, thereby reducing the preparation cost and energy consumption of the existing multi-level pore molecular sieve.

[0010] Preferably, the attapulgite-based multi-level pore HZSM-5 molecular sieve supported iron-based catalyst is prepared by the following steps:

[0011] (1) adding acid-modified attapulgite to a sodium hydroxide solution and stirring the solution at 50° C. to 80° C. for 0.5 to 2 hours, cooling the solution to room temperature and adding tetrapropylammonium bromide aqueous solution dropwise thereto, stirring and dispersing the solution for 5 to 10 minutes, adjusting the solution pH to 9.5 to 10.5, and continuing stirring for 24 to 48 hours to obtain a microporous precursor solution;

[0012] (2) adding three-dimensional ordered macroporous polymethyl methacrylate and hexadecyltrimethylammonium bromide to the microporous precursor solution obtained in step (1), and continuing stirring for 2 to 5 hours, transferring to a hydrothermal reaction vessel, and hydrothermally reacting at 150° C. to 200° C. for 2 to 4 days, washing and drying after cooling, and calcining at 500° C. to 700° C. for 4 to 6 hours to obtain a NaZSM-5 molecular sieve with nano-multilevel pores;

[0013] (3) grinding and sieving the NaZSM-5 molecular sieve, adding ammonium nitrate or ammonium chloride solution to condense and reflux at 80° C. to 100° C. for 3 to 5 hours, washing and drying, and calcining at 500° C. to 700° C. for 4 to 6 hours to obtain a HZSM-5 molecular sieve with nano-multilevel pores;

[0014] (4) According to the iron loading, a corresponding amount of iron salt is weighed and mixed with the nano-multilevel porous HZSM-5 molecular sieve obtained in step (3), and deionized water is slowly added to completely wet the mixture of the iron salt and the molecular sieve. After stirring and impregnation, the mixture is dried and calcined at 350° C. to 450° C. for 3 to 5 hours to obtain the target catalyst.

[0015] In step (1), nitric acid is preferably used to adjust the solution pH to 9.5 to 10.5.

[0016] Further preferably, the preparation method of the acid-modified attapulgite described in step (1) is: weigh 10 parts by mass of natural attapulgite and add 50 to 80 parts by mass of sulfuric acid with a concentration of 3 to 5 mol / L, stir and react at 60°C to 90°C for 24 to 48 hours, then filter, wash to neutrality, and dry to constant weight to obtain acid-modified attapulgite. The contents of SiO2 and Al2O3 in the acid-modified attapulgite are 85.6% to 91.3% and 2.8% to 5.9%, respectively.

[0017] Further preferably, the molar ratio of the sodium hydroxide described in step (1) to the SiO2 contained in the acid-modified attapulgite is 1 to 2:1, and the concentration of the sodium hydroxide solution is 0.5 to 2 mol / L; the molar ratio of the tetrapropylammonium bromide to the Al2O3 contained in the acid-modified attapulgite is 5 to 20:1, and the molar ratio of the total water content of the tetrapropylammonium bromide aqueous solution and the above-mentioned sodium hydroxide solution to the Al2O3 contained in the acid-modified attapulgite is 800 to 10000:1.

[0018] Further preferably, the three-dimensional ordered macroporous polymethyl methacrylate described in step (2) is prepared by centrifugal self-assembly method, has a particle size of 200 to 800 nm, and the mass ratio of its addition amount to the tetrapropylammonium bromide added in step (1) is 0.2 to 1:1.

[0019] More preferably, the amount of hexadecyltrimethylammonium bromide added in step (2) is 5% to 20% of the molar amount of SiO2 contained in the acid-modified attapulgite.

[0020] Further preferably, the grinding and sieving size of the NaZSM-5 molecular sieve described in step (3) is 100-200 mesh, the concentration of the ammonium nitrate or ammonium chloride aqueous solution is 0.1-0.5 mol / L, and the volume mass ratio of the ammonium nitrate or ammonium chloride aqueous solution to the NaZSM-5 molecular sieve is 10-20 mL / g.

[0021] More preferably, the iron loading in step (4) is 5% to 20%, and the iron salt is selected from one of ferric nitrate, ferric acetate and ferric chloride.

[0022] The present invention also protects the use of the attapulgite-based multi-level pore HZSM-5 molecular sieve-supported iron-based catalyst in preparing aromatics from synthesis gas.

[0023] Preferably, the method comprises the following steps: tabletting, crushing and sieving the catalyst powder into 60-80 mesh particles, and uniformly mixing the catalyst powder with 40-60 mesh quartz sand in a volume ratio of 1:1, and then loading the mixture into a fixed bed reactor; reducing the catalyst with hydrogen at 350°C to 450°C for 3 to 6 hours, introducing a synthesis gas with a molar ratio of H2:CO of 0.5 to 3:1, and reacting the mixture at a reaction temperature of 250°C to 400°C, a reaction pressure of 0.5 to 4.0 MPa, and a volume space velocity of 1000 to 10000 h -1 The synthesis gas is converted into aromatic hydrocarbons under certain conditions, wherein the aromatic hydrocarbons are any one of benzene, toluene, xylene, trimethylbenzene, ethylbenzene, methylethylbenzene and diethylbenzene, or a mixture of two or more thereof.

[0024] More preferably, the reaction conditions are reaction temperature 300°C to 360°C, reaction pressure 3.0 to 4.0 MPa, volume space velocity 3000 to 5000 h -1 .

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The nano-multi-level porous HZSM-5 molecular sieve loaded with iron-based catalyst is prepared using natural attapulgite as raw material, avoiding the use of chemical reagents such as tetraethyl orthosilicate and aluminum isopropoxide. At the same time, the synergistic effect of template agent and structure directing agent is utilized to realize the in-situ formation of microporous-mesoporous multi-level porous structure molecular sieve, thereby reducing the preparation cost and energy consumption of existing multi-level porous molecular sieves.

[0027] (2) The catalyst prepared by the catalyst preparation method provided by the present invention, on the one hand, has a multi-level pore structure that provides an ideal channel for the conversion and escape of CO raw material molecules and aromatic product molecules, thereby promoting the improvement of CO conversion rate and aromatic selectivity; on the other hand, Fe, Na, K, etc. in attapulgite are used as structural additives to regulate the acidity and acid content of the HZSM-5 molecular sieve, thereby effectively reducing catalyst carbon deposition and extending the service life of the catalyst.

[0028] (3) Using the catalyst provided by the present invention, under preferred conditions, a CO single-pass conversion rate of more than 90% and an aromatics selectivity of 60% can be achieved, and the molecular sieve does not require a post-treatment process. The catalyst preparation process is simple and low-cost, and has good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope image of the nano-multilevel pore HZSM-5 molecular sieve prepared in Example 1.

[0030] Figure 2 This is the pore size distribution diagram of the nano-multi-level pore HZSM-5 molecular sieve prepared in Example 1. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below with reference to the examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples where specific conditions are not specified are generally based on conventional conditions in the art or conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are considered to be raw materials and reagents that can be obtained through commercial channels such as conventional markets.

[0032] The invention adopts acid-modified attapulgite as a raw material to synthesize HZSM-5 molecular sieve, wherein the contents of SiO2 and Al2O3 contained in the HZSM-5 molecular sieve are measured by using an X-ray fluorescence spectrometer (XRF).

[0033] Example 1

[0034] (1) The attapulgite-based multi-level pore HZSM-5 molecular sieve supported iron-based catalyst is prepared by the following steps:

[0035] 1) Modification of attapulgite: 10 g of attapulgite ore was added to 50 g of 3 mol / L sulfuric acid, stirred and reacted at 90°C for 24 hours, and then filtered, washed to neutrality, and dried to constant weight to obtain acid-modified attapulgite. The SiO2 and Al2O3 contents in the modified attapulgite were measured by XRF to be 88.7% and 4.1%, respectively.

[0036] 2) Preparation of microporous precursor solution: weigh 4.73g NaOH, add 59.1mL deionized water to prepare an alkaline solution with a NaOH concentration of 2mol / L, add 8g modified attapulgite thereto, and stir and react at 80°C for 0.5 hours; weigh 17.13g tetrapropylammonium bromide, add 519.9mL deionized water to prepare a solution, add it dropwise to the above mixed system at room temperature, stir and disperse for 5 minutes, adjust the solution pH to 10.5 with nitric acid, and continue stirring for 48 hours to obtain a microporous precursor solution;

[0037] 3) Preparation of nano-multi-level pore NaZSM-5 molecular sieve: 8.57 g of three-dimensional ordered macroporous polymethyl methacrylate and 4.3 g of hexadecyltrimethylammonium bromide were added to the microporous precursor solution obtained in step 2) and stirred for 2 hours, then transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, and hydrothermally reacted at 200° C. for 2 days. After cooling, the mixture was washed, dried, and calcined at 500° C. for 4 hours to obtain a nano-multi-level pore NaZSM-5 molecular sieve.

[0038] 4) Preparation of nano-multi-level pore HZSM-5 molecular sieve: Weigh 5g of the NaZSM-5 molecular sieve obtained in step 3), add 100mL of 0.1mol / L ammonium chloride aqueous solution, condense and reflux at 90℃ for 3 hours, wash and dry, and calcine at 500℃ for 6 hours to obtain nano-multi-level pore HZSM-5 molecular sieve. The scanning electron microscope image and pore size distribution diagram of HZSM-5 molecular sieve are shown in the figure. Figure 1 and Figure 2 shown.

[0039] 5) Preparation of nano-multilevel porous HZSM-5 molecular sieve loaded with 10% Fe catalyst: According to the iron loading amount, weigh the corresponding mass of ferric nitrate and mix it with the nano-multilevel porous HZSM-5 molecular sieve, slowly add deionized water to just completely soak the ferric nitrate and molecular sieve mixture, stir and soak for 5 hours, then dry, and calcine at 350°C for 5 hours to obtain the target catalyst.

[0040] (2) Synthesis gas conversion to aromatics: 3 g of the catalyst prepared in step (1) was weighed, granulated and uniformly mixed with 3 g of quartz sand with a particle size of 40-60 mesh, and loaded into a fixed bed reactor. After reduction with hydrogen at 400° C. for 3 hours, synthesis gas with a molar ratio of H2:CO of 3:1 was introduced. The reaction temperature was 250° C. to 400° C., the reaction pressure was 4.0 MPa, and the volume space velocity was 1000 h / min. -1 The synthesis gas was converted into aromatics under the following conditions. The composition of the reaction tail gas and liquid products was analyzed by gas chromatography, and the results of the catalyst performance evaluation are shown in Table 1.

[0041] Table 1

[0042]

[0043] C2-C4 represents alkanes and alkenes, C 5+ * Indicates C without aromatics 5+ Hydrocarbons.

[0044] It can be seen from Table 1 that as the reaction temperature increases, the CO conversion rate gradually increases, the CO2 selectivity gradually decreases, and the aromatics selectivity first gradually increases and then changes little. Therefore, the reaction temperature is preferably 300°C to 360°C.

[0045] Comparative Example 1:

[0046] NaZSM-5 molecular sieve was prepared by referring to the preparation method of conventional ZSM-5 molecular sieve disclosed in Example 1 of patent CN 110342535 A, and then a catalyst with the same Fe loading of 10% was prepared by the preparation method of HZSM-5 molecular sieve and its supported iron-based catalyst disclosed in steps 4) and 5) of Example 1 of the present invention, and aromatics synthesis was carried out at 300° C. and other parameters were the same as those in Example 1. The composition of the reaction tail gas and liquid product was analyzed by gas chromatograph, and the results showed that the CO conversion rate was 59.7% and the aromatics selectivity was 31.5%. Therefore, the aromatics synthesis performance of the HZSM-5 molecular sieve supported iron-based catalyst prepared by modified attapulgite as silicon source and aluminum source is significantly better than that of the HZSM-5 molecular sieve supported iron-based catalyst prepared by the conventional method. This is because the HZSM-5 molecular sieve prepared by the conventional method is mainly a microporous structure, while the attapulgite-based multi-level pore HZSM-5 molecular sieve has a microporous-mesoporous multi-level pore structure, which is more beneficial to the conversion rate of CO and the synthesis of aromatics.

[0047] Embodiment 2:

[0048] (1) The attapulgite-based multi-level pore HZSM-5 molecular sieve supported iron-based catalyst is prepared by the following steps:

[0049] 1) Modification of attapulgite: 10 g of attapulgite ore was added to 80 g of 5 mol / L sulfuric acid, stirred and reacted at 60°C for 48 hours, and then filtered, washed to neutrality, and dried to constant weight to obtain acid-modified attapulgite. The SiO2 and Al2O3 contents in the acid-modified attapulgite were measured by XRF to be 91.3% and 2.8%, respectively.

[0050] 2) Preparation of microporous precursor solution: weigh 7.3g NaOH, add 182.5mL deionized water to prepare an alkaline solution with a NaOH concentration of 1mol / L, add 6g acid-modified attapulgite thereto, and stir and react at 50°C for 2 hours; weigh 2.2g tetrapropylammonium bromide, add 54.8mL deionized water to prepare a solution, add it dropwise to the above mixed system at room temperature, stir and disperse for 10 minutes, use nitric acid to adjust the solution pH to 9.5, and continue stirring for 24 hours to obtain a microporous precursor solution.

[0051] 3) Preparation of nano-multi-level pore NaZSM-5 molecular sieve: After adding 2.2 g of three-dimensional ordered macroporous polymethyl methacrylate and 6.65 g of hexadecyltrimethylammonium bromide to the microporous precursor solution obtained in step 2), stirring was continued for 5 hours, and then transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene, and hydrothermally reacted at 150° C. for 4 days. After cooling, the mixture was washed and dried, and calcined at 700° C. for 6 hours to obtain a nano-multi-level pore NaZSM-5 molecular sieve.

[0052] 4) Preparation of nano-multilevel pore HZSM-5 molecular sieve: Weigh 4 g of the NaZSM-5 molecular sieve obtained in step 3), add 40 mL of 0.5 mol / L ammonium chloride aqueous solution, condense and reflux at 90° C. for 5 hours, then wash and dry, and calcine at 700° C. for 4 hours to obtain a nano-multilevel pore HZSM-5 molecular sieve.

[0053] 5) Preparation of nano-multilevel porous HZSM-5 molecular sieve loaded with 20% Fe catalyst: According to the iron loading amount, weigh the corresponding mass of ferric chloride and mix it with the nano-multilevel porous HZSM-5 molecular sieve, slowly add deionized water to just completely soak the ferric chloride and molecular sieve mixture, stir and soak for 12 hours, then dry, and calcine at 450°C for 3 hours to obtain the target catalyst.

[0054] (2) Synthesis gas conversion to aromatics: 3 g of the catalyst prepared in step (1) was weighed, granulated and uniformly mixed with 3 g of quartz sand with a particle size of 40-60 mesh, and loaded into a fixed bed reactor. After reduction with hydrogen at 350° C. for 6 hours, synthesis gas with a molar ratio of H2:CO of 2:1 was introduced. The reaction temperature was 360° C., the reaction pressure was 0.5-4.0 MPa, and the volume space velocity was 3000 h / min. -1 The synthesis gas was converted into aromatics under the following conditions. The composition of the reaction tail gas and liquid products was analyzed by gas chromatography, and the catalyst performance evaluation results are shown in Table 2.

[0055] Table 2

[0056]

[0057]

[0058] C2-C4 represents alkanes and alkenes, C 5+ * Indicates C without aromatics 5+ Hydrocarbons.

[0059] It can be seen from Table 2 that as the reaction pressure increases, the CO conversion rate gradually increases, the CO2 selectivity gradually decreases, and the aromatics selectivity gradually increases. Therefore, the reaction pressure is preferably 3.0-4.0 MPa.

[0060] Comparative Example 2:

[0061] Referring to steps 1) and 2) in the above Example 2, a microporous precursor solution was prepared, and then in the process of preparing the NaZSM-5 molecular sieve in step 3), only three-dimensional ordered macroporous polymethyl methacrylate (PMMA) or hexadecyltrimethylammonium bromide (CTAB) was added, and the HZSM-5 molecular sieve-supported iron-based catalyst was obtained while keeping other synthesis parameters and steps consistent with Example 2, and aromatics synthesis was carried out under the reaction conditions of 3.0 MPa and other parameters being the same as those in Example 1. The composition of the reaction tail gas and the liquid product was analyzed by gas chromatograph, and the results are shown in Table 3.

[0062] Table 3

[0063]

[0064] C2-C4 represents alkanes and alkenes, C 5+ * Indicates C without aromatics 5+ Hydrocarbons.

[0065] It can be seen from Table 3 that the CO conversion rate and aromatics selectivity of the HZSM-5 molecular sieve supported Fe catalyst prepared by adding only PMMA or CTAB are significantly lower than those of the HZSM-5 molecular sieve supported Fe catalyst prepared by adding PMMA and CTAB at the same time, which fully reflects the synergistic effect of PMMA and CTAB in the preparation of nano-multilevel pore HZSM-5 molecular sieve.

[0066] Embodiment 3:

[0067] (1) The attapulgite-based multi-level pore HZSM-5 molecular sieve supported iron-based catalyst is prepared by the following steps:

[0068] 1) Modification of attapulgite: 10 g of attapulgite ore was added to 60 g of 3 mol / L sulfuric acid, stirred and reacted at 80°C for 24 hours, and then filtered, washed to neutrality, and dried to constant weight to obtain acid-modified attapulgite. The SiO2 and Al2O3 contents in the acid-modified attapulgite were measured by XRF to be 85.6% and 5.9%, respectively.

[0069] 2) Preparation of microporous precursor solution: weigh 8.52g NaOH, add 106.5mL deionized water to prepare an alkaline solution with a NaOH concentration of 2mol / L, add 10g acid-modified attapulgite thereto, and stir and react at 70°C for 1 hour; weigh 15.44g tetrapropylammonium bromide, add 102.3mL deionized water to prepare a solution, add it dropwise to the above mixed system at room temperature, stir and disperse for 8 minutes, adjust the solution pH to 10.0 with nitric acid, and continue stirring for 36 hours to obtain a microporous precursor solution;

[0070] 3) Preparation of nano-multi-level pore NaZSM-5 molecular sieve: 3.09 g of three-dimensional ordered macroporous polymethyl methacrylate and 2.59 g of hexadecyltrimethylammonium bromide were added to the microporous precursor solution obtained in step 2) and stirred for 4 hours. The mixture was transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 180° C. for 3 days. After cooling, the mixture was washed and dried, and calcined at 600° C. for 5 hours to obtain a nano-multi-level pore NaZSM-5 molecular sieve.

[0071] 4) Preparation of nano-multilevel pore HZSM-5 molecular sieve: Weigh 5 g of the NaZSM-5 molecular sieve obtained in step 3), add 75 mL of 0.3 mol / L ammonium nitrate aqueous solution, condense and reflux at 90° C. for 4 hours, then wash and dry, and calcine at 600° C. for 5 hours to obtain a nano-multilevel pore HZSM-5 molecular sieve.

[0072] 5) Preparation of nano-multilevel porous HZSM-5 molecular sieve loaded with 5% Fe catalyst: According to the iron loading amount, weigh the corresponding mass of ferric acetate and mix it with the nano-multilevel porous HZSM-5 molecular sieve, slowly add deionized water to make the mixture of ferric acetate and molecular sieve just completely soaked, stir and soak for 10 hours, then dry, and calcine at 400°C for 4 hours to obtain the target catalyst.

[0073] (2) Synthesis gas conversion to aromatics: 3 g of the catalyst prepared in step (1) was weighed, granulated and uniformly mixed with 3 g of quartz sand with a particle size of 40-60 mesh, loaded into a fixed bed reactor, reduced with hydrogen at 450° C. for 6 hours, and then introduced with synthesis gas with a molar ratio of H2:CO of 0.5:1. The reaction temperature was 350° C., the reaction pressure was 4.0 MPa, and the volume space velocity was 1000-10000 h / min. -1 The synthesis gas was converted into aromatics under the following conditions. The composition of the reaction tail gas and liquid products was analyzed by gas chromatography, and the results of the catalyst performance evaluation are shown in Table 4.

[0074] Table 4

[0075]

[0076] C2-C4 represents alkanes and alkenes, C 5+ * Indicates C without aromatics 5+ Hydrocarbons.

[0077] It can be seen from Table 4 that with the increase of reaction space velocity, CO conversion rate decreases rapidly, CO2 selectivity decreases first and then increases, and aromatics selectivity increases first and then decreases. Therefore, the reaction space velocity is preferably 3000-5000h -1 .

[0078] The description of the above embodiments is only used to help understand the technical solution and core ideas of the present invention. It should be pointed out that for technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. These improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. An attapulgite-based multi-level pore HZSM-5 molecular sieve supported iron-based catalyst, characterized in that: It is prepared by the following steps: (1) adding acid-modified attapulgite to a sodium hydroxide solution and stirring the solution at 50° C. to 80° C. for 0.5 to 2 hours, cooling the solution to room temperature, and adding tetrapropylammonium bromide aqueous solution dropwise thereto. After stirring and dispersing, adjusting the solution pH to 9.5 to 10.5, and continuing stirring for 24 to 48 hours to obtain a microporous precursor solution; (2) adding three-dimensional ordered macroporous polymethyl methacrylate and hexadecyltrimethylammonium bromide to the microporous precursor solution obtained in step (1), and continuing stirring for 2 to 5 hours, transferring to a hydrothermal reaction vessel, and hydrothermally reacting at 150° C. to 200° C. for 2 to 4 days, washing and drying after cooling, and calcining at 500° C. to 700° C. for 4 to 6 hours to obtain a NaZSM-5 molecular sieve with nano-multilevel pores; (3) grinding and sieving the NaZSM-5 molecular sieve, adding ammonium nitrate or ammonium chloride solution to condense and reflux at 80° C. to 100° C. for 3 to 5 hours, washing and drying, and calcining at 500° C. to 700° C. for 4 to 6 hours to obtain a HZSM-5 molecular sieve with nano-multilevel pores; (4) According to the iron loading, a corresponding amount of iron salt is weighed and mixed with the nano-multilevel porous HZSM-5 molecular sieve obtained in step (3), and deionized water is slowly added to completely wet the mixture of the iron salt and the molecular sieve. After stirring and impregnation, the mixture is dried and calcined at 350° C. to 450° C. for 3 to 5 hours to obtain the target catalyst.

2. The attapulgite-based multi-level pore HZSM-5 molecular sieve supported iron-based catalyst according to claim 1, characterized in that: The preparation method of the acid-modified attapulgite described in step (1) is as follows: weigh 10 parts by mass of natural attapulgite, add 50 to 80 parts by mass of sulfuric acid with a concentration of 3 to 5 mol / L, stir and react at 60° C. to 90° C. for 24 to 48 hours, then filter, wash to neutrality, and dry to constant weight to obtain acid-modified attapulgite.

3. The attapulgite-based multi-level pore HZSM-5 molecular sieve supported iron-based catalyst according to claim 1, characterized in that: The molar ratio of the sodium hydroxide described in step (1) to the SiO2 contained in the acid-modified attapulgite is 1-2:1, and the concentration of the sodium hydroxide solution is 0.5-2 mol / L; the molar ratio of the tetrapropylammonium bromide to the Al2O3 contained in the acid-modified attapulgite is 5-20:1, and the molar ratio of the total water content of the tetrapropylammonium bromide aqueous solution and the above-mentioned sodium hydroxide solution to the Al2O3 contained in the acid-modified attapulgite is 800-10000:

1.

4. The attapulgite-based multi-level pore HZSM-5 molecular sieve supported iron-based catalyst according to claim 1, characterized in that: The three-dimensional ordered macroporous polymethyl methacrylate described in step (2) is prepared by centrifugal self-assembly method, and has a particle size of 200 to 800 nm. The mass ratio of the three-dimensional ordered macroporous polymethyl methacrylate added to the tetrapropylammonium bromide added in step (1) is 0.2 to 1:

1.

5. The attapulgite-based multi-level pore HZSM-5 molecular sieve supported iron-based catalyst according to claim 1, characterized in that: The amount of hexadecyltrimethylammonium bromide added in step (2) is 5% to 20% of the molar amount of SiO2 contained in the acid-modified attapulgite.

6. The attapulgite-based multi-level pore HZSM-5 molecular sieve supported iron-based catalyst according to claim 1, characterized in that: The grinding and sieving size of the NaZSM-5 molecular sieve described in step (3) is 100-200 mesh, the concentration of the ammonium nitrate or ammonium chloride aqueous solution is 0.1-0.5 mol / L, and the volume mass ratio of the ammonium nitrate or ammonium chloride aqueous solution to the NaZSM-5 molecular sieve is 10-20 mL / g.

7. The attapulgite-based multi-level pore HZSM-5 molecular sieve supported iron-based catalyst according to claim 1, characterized in that: The iron loading amount in step (4) is 5% to 20%, and the iron salt is selected from one of ferric nitrate, ferric acetate and ferric chloride.

8. Use of the attapulgite-based multi-level pore HZSM-5 molecular sieve supported iron-based catalyst according to claim 1 in the preparation of aromatics from synthesis gas.

9. The use according to claim 8, characterized in that: The method comprises the following steps: tabletting, crushing and screening the catalyst powder into 60-80 mesh particles, uniformly mixing the catalyst powder with 40-60 mesh quartz sand in a volume ratio of 1:1, and then loading the mixture into a fixed bed reactor; reducing the catalyst with hydrogen at 350-450°C for 3-6 hours, introducing synthesis gas with a molar ratio of H2:CO of 0.5-3:1, and reacting the mixture at a reaction temperature of 250-400°C, a reaction pressure of 0.5-4.0 MPa, and a volume space velocity of 1000-10000 h -1 The synthesis gas is converted into aromatic hydrocarbons under certain conditions, wherein the aromatic hydrocarbons are any one of benzene, toluene, xylene, trimethylbenzene, ethylbenzene, methylethylbenzene and diethylbenzene, or a mixture of two or more thereof.

Citation Information

Patent Citations

  • Catalyst for directly preparing synthesis gas into aromatic compounds and preparation method and application of catalyst

    CN105944751A

  • Catalyst for preparing arene from synthesis gas through one-step conversion and preparation method of catalyst

    CN106215972A

  • A catalyst for the direct production of aromatics from syngas, its preparation and application

    CN106268924B

  • Catalyst for high-selectivity preparation of light aromatic hydrocarbon by using synthesis gas and preparation method thereof

    CN106540740A

  • Catalyst for preparing arene from synthesis gas and use method of catalyst

    CN106607083A